2006
DOI: 10.1073/pnas.0606137103
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal storage disease upon disruption of the neuronal chloride transport protein ClC-6

Abstract: Mammalian CLC proteins function as Cl ؊ channels or as electrogenic Cl ؊ ͞H ؉ exchangers and are present in the plasma membrane and intracellular vesicles. We now show that the ClC-6 protein is almost exclusively expressed in neurons of the central and peripheral nervous systems, with a particularly high expression in dorsal root ganglia. ClC-6 colocalized with markers for late endosomes in neuronal cell bodies. The disruption of ClC-6 in mice reduced their pain sensitivity and caused moderate behavioral abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
230
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(237 citation statements)
references
References 40 publications
7
230
0
Order By: Relevance
“…This neurodegeneration is not associated with the massive intraneuronal deposits of lysosomal storage material found in mice lacking ClC-6 (Poët et al, 2006), ClC-7 (Kasper et al, 2005), or Ostm1 (Lange et al, 2006). Although CNS degeneration is the salient feature of ClC-3 knock-out (KO) mice (Stobrawa et al, 2001;Dickerson et al, 2002;Yoshikawa et al, 2002), ClC-3 is expressed in many other tissues (Kawasaki et al, 1994;Borsani et al, 1995;Stobrawa et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This neurodegeneration is not associated with the massive intraneuronal deposits of lysosomal storage material found in mice lacking ClC-6 (Poët et al, 2006), ClC-7 (Kasper et al, 2005), or Ostm1 (Lange et al, 2006). Although CNS degeneration is the salient feature of ClC-3 knock-out (KO) mice (Stobrawa et al, 2001;Dickerson et al, 2002;Yoshikawa et al, 2002), ClC-3 is expressed in many other tissues (Kawasaki et al, 1994;Borsani et al, 1995;Stobrawa et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The disruption of vesicular CLCs has diverse effects including impaired renal endocytosis and kidney stones with a loss of ClC-5 (Lloyd et al, 1996;Piwon et al, 2000;Wang et al, 2000), lysosomal storage disease with a loss of ClC-6 (Poët et al, 2006), and osteopetrosis associated with lysosomal storage disease with a loss of either ClC-7 (Kornak et al, 2001;Kasper et al, 2005) or its ␤-subunit Ostm1 (Lange et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies suggest that other proteins of known function may be candidates for yet unclassified human NCLs. For instance, mice deficient in cathepsin F had previously been shown to develop late-onset neuronal ceroid-lipofuscinosis thus predicting CLN13 [12], and deficiencies of chloride channel proteins CLC-3, CLC-6, and CLC-7 produce neuronal ceroid-lipofuscinosis phenotypes in mice [13][14][15]. A truncating mutation in ATP13A2 that encodes an ATPase transporter of inorganic cations has been described in Tibetan terriers with adult onset NCL [16].…”
Section: Biological/functional Classificationmentioning
confidence: 99%
“…It has been shown that the pH gradient between cytosol and vesicular content is generated by vacuolar H + ATPases 1 , coupled to vesicular ClC chloride transporters 2 . Both in knock-out (KO) mice and human patients, the importance of these transporters has been highlighted by the heavy phenotypes caused by mutations in their genes [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%